Horse Welfare During Equine Chorionic Gonadotropin (eCG) Production - Manteca Vilanova, Xavier (Animals (Basel), 2019)
SIMPLE SUMMARY: Equine chorionic gonadotropin or eCG is an important hormone produced by the placenta of pregnant mares and extracted from the blood of these same mares. This hormone is commonly used to enhance reproduction of pigs, dairy cows, sheep, beef cows, and goats. There are currently no alternative sources of this hormone. Horse welfare problems may arise if too much blood is collected at one time or during repeated collections or if the mares are not managed well. In some countries, mares are aborted several months into the pregnancy to improve efficiency since this permits them to become pregnant a second time in one year. We discuss approaches to protect the welfare of pregnant mares kept for eCG production. ABSTRACT: Collection of blood from pregnant mares for extraction of equine chorionic gonadotropin (eCG) is a critical but relatively unknown and poorly regulated practice in the countries in which it occurs. Equine chorionic gonadotropin is a hormone that is widely used to enhance reproductive performance and management of dairy and beef cattle, sheep, goats, and pigs kept under intensive housing systems. eCG is extracted from the blood of brood mares between days 40–120 of gestation. Although alternatives have been sought, there is currently no efficacious replacement, natural or synthetic, for eCG. Recently, several animal welfare organizations have voiced concerns over the condition and treatment of pregnant mares kept for eCG production in some countries. Animal welfare issues may arise if mares are bled too frequently or if too much blood is collected at any time. In addition, these mares tend to be managed extensively on pastures with minimal veterinary oversight and they may be poorly desensitized and habituated to handling and other practices. This can lead to serious injuries and even death when mares are brought in for bleeding. This paper reviews the process of blood collection for eCG extraction and provides recommendations for ensuring mare welfare.